RESPON BIBIT KELAPA SAWIT (Elaeis gueneensis Jacq.) PADA BERBAGAI UMUR TERHADAP LAMA GENANGAN AIR - Dimas Parikno; Gunawan Tabrani; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research conducted to find out how palm oil seedlingsstage to response length waterloggingstress, to aims the best stage of palm oil seedlings that can resist waterlogging stress.This research was conducted at the Green House of Agriculture Faculty, RiauUniversity, sub-districsSimpang Baru,Tampan Districs, Pekanbaru from July to November 2015. The design of this research was Factorial Completely Randomized Design for 2 factors and 3 replication.The first factor was palm seedlings age:u0 = 3th month, u1 = 5th month, and u2 = 7th month, and the second factor was the length of waterlogging stress:g0 = without waterlogging stress, g1 = 20 days waterlogging stress and g0 = 40 days waterlogging stress.The parameter observed are: seedling height, number of leaf, stemdiameter, primary root length, number of primary root, root-shootratio, qualityseedlingindex and dry weight matter. The results showed that no interaction between seedling stageswithwaterlogging length stressor length of waterlogging stress toall of growth components palm oil seedling except seedling height. The growth palm oil seedling determined of palm oil seedling stages except primary root length. The height of 5th month palm oil seedlings reduced against 20 days of waterlogging stress, but increase againts to 40 daysof waterlogging stress.Keywords: palm oil seedlings, waterlogging stress, growth components.